The Role Of Disruptive Technology In Interactive Furniture Design (Al-Academy, 2023)
The substitutional technology has made a huge shift in the lives of users، and it has caused many transformations in all levels and levels، and those that resulted in a boom in the furniture industry، and therefore interactive furniture appeared as a result of the development brought about by the substitutional technology and the close relationship between users and electronic devices that are developing Continuously، and the need to keep pace with modern developments globally in the furniture industry.Interactive furniture is the pinnacle of technological progress that humanity has reached، as substitutional technology systems have been used in furniture to serve the user، as access to user comfort must be the biggest task of the design process، as the advancement of different technologies and design systems is reflected in the design and development of furniture as a service to the comfort of individuals.The use of the concept of substitutional technology and its applications in the design of interactive furniture and the importance of identifying what the substitutional and logical technology is in the surroundings that occur in interactive furniture in terms of formal، aesthetic and functional aspects